Mechanistic Studies of CO2 Cycloaddition Reaction Catalyzed by Amine-Functionalized Ionic Liquids - Chen, Jian; Gao, Han; Ding, Tong; Ji, Liangzheng; Zhang, John Z. H.; Gao, Guohua; Xia, Fei (Frontiers in Chemistry, 2019)
The homogeneous cycloaddition reaction of CO2 and epichlorohydrin catalyzed by amine-functionalized ionic liquid (AFIL) to yield cyclic carbonate is reported in this study. The AFIL has the dual function of ionic liquid and organic base. The experimental study indicates that AFIL can efficiently catalyze the conversion of CO2 and epichlorohydrin to the product 3-chloro-1,2-propylene. The mechanistic study based on DFT calculations reveals that the imidazolium ring in AFIL primarily catalyzes the ring-opening reaction of epichlorohydrin, while the protonated amine group is responsible for stabilizing the Br- anion in the nucleophilic attack. This study provides a deep insight into the catalytic roles of AFIL and also inspires us to design efficient dual function catalysts for CO2 utilization.